Tari Lembaran Persegi: Makna Filosofi Maindang Manampih Bareh Disisiahan Atah Ciek-Ciek - Reza Maulidil Akbar; Rasmida Rasmida; Donny Osmond; Wardi Metro (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
The dance work "Square Sheet" is inspired by the meaning of the Minangkabau proverb, namely maindang manampih bareh disisahan or ciek-ciek, which means the importance of full awareness of what is done and the impact caused, aware of choices and decisions. Based on this meaning, the author is interested in making that meaning as a source of inspiration for the dance work entitled "Square Sheet". This interest is based on the author seeing that at this time the public is no longer choosing leaders with a decent track record but the public attaches more importance to closeness and wealth. Related to that, the worker focuses on the issue of full awareness of the decisions made and the impact caused, through the body's physical, mental, and emotional response. To realize the dance work, the author chose the piriang koto sani dance as a foothold in the preparation of the work. The worker interprets into the form of group choreography which is worked in three grooves of atmosphere. The theories used in this work are social construction theory and choreography theory. The method used is the method written by Alma M. Hawkins in the book choreography of form, technique, and content of Sumandiyo Hadi's translated work is field observation data collection, data processing, literature study, exploration, improvisation, formation and evaluation. This work is performed by two female dancers and four male dancers, the music is used to strengthen the atmosphere that the worker is based on from the music from the traditional Minangkabau which is worked by the composer according to the concept of the work. Other than that, of course, it cannot be separated from the nine elements of the tar composition. This work has been displayed at the Boestanoel Arifin Adam Auditorium of the Indonesian Padangpanjang Art Institute on January 15, 2026.